Classical and applied mathematics in secondary school - Kézi, Csaba (International Journal of Engineering and Management Sciences, 2019)
In a secondary school I wrote a test with similar abilites student. In one class students had to solved applied mathematics exercises, in other class there were pure mathematics exercises. I anayzed the results.